3x-4-4x=6

Simple and best practice solution for 3x-4-4x=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4-4x=6 equation:


Simplifying
3x + -4 + -4x = 6

Reorder the terms:
-4 + 3x + -4x = 6

Combine like terms: 3x + -4x = -1x
-4 + -1x = 6

Solving
-4 + -1x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -1x = 6 + 4

Combine like terms: -4 + 4 = 0
0 + -1x = 6 + 4
-1x = 6 + 4

Combine like terms: 6 + 4 = 10
-1x = 10

Divide each side by '-1'.
x = -10

Simplifying
x = -10

See similar equations:

| 4W=-29 | | -3+quaterz=1 | | -6(v+4)+4v+6=7v+6 | | 2(5x+1)=4x-8x | | 3xx+15x-6=180 | | 4x+4+6x=64 | | 6x-3=6(x+3) | | -0.5x+7.68=-0.7x+6.48 | | 2p+9q=36 | | 16(2x-7)=4(8x+5) | | 6x+2x-5=35 | | A=a+b+c/3 | | 2(5x+6)=-33+35 | | x/10=5/12 | | x/9=36 | | 5/8x+1/16x=11/16x | | 18+10x+x^2=0 | | 2(w+5)= | | 5s+2(1/5)=3/5s+2 | | 51-3x=24x+15 | | 5x+3=14x-66 | | -9=5+2x | | -0.8x+0.3x+7=6 | | (x-100)/(9(5x-50))=0 | | -17-15x=-10x-40 | | R=E/I | | (x-100)/9(5x-50)=0 | | 90=1.5t^2 | | 3m+7-8= | | 5z-7-2z+4=0 | | 10x-36=-2x-20 | | 5x+73=11x+12 |

Equations solver categories